Electroerosive Powder Obtained from Alloy VK8 Waste into Butanol - E.V. Ageev; A.Yu. Altukhov; S.V. Khardikov; S.S. Gulidin; A.N. Novikov (Журнал нано- та електронної фізики)
The results of studies of the properties of the powders obtained by electroerosive dispersing of the hard alloy wastes of mark VK8 in butanol. It is found that the powder particles obtained by electroerosive dispersing of waste carbide grade VK8 in butyl alcohol, consist of the following major elements: W, Co, Fe, C and O.